2007
DOI: 10.1177/155892500700200104
|View full text |Cite
|
Sign up to set email alerts
|

Strength Optimization of Thermally Bonded Spunbond Nonwovens

Abstract: Recent research on all aspects of thermally point bonded nonwovens has led to considerable improvements in the understanding of material requirements for these nonwovens, the changes that occur during bonding and the resultant deterioration of the mechanical properties of the nonwoven materials. This paper addresses how one may use a bicomponent fiber technology to overcome the shortcomings of the thermal bonding and obtain high strength spunbond fabrics. In particular, we present the utility of islands-in-the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 22 publications
0
20
0
2
Order By: Relevance
“…We do not see a justifiable reason why tensile properties would increase and then decrease with island count. Previously, we have shown that island fiber properties do not change at higher island counts [21,25]. Any significant changes therefore, may be due to structural variations, the degree of splitting and entanglement.…”
Section: Role Of Island Count On Performancementioning
confidence: 78%
See 3 more Smart Citations
“…We do not see a justifiable reason why tensile properties would increase and then decrease with island count. Previously, we have shown that island fiber properties do not change at higher island counts [21,25]. Any significant changes therefore, may be due to structural variations, the degree of splitting and entanglement.…”
Section: Role Of Island Count On Performancementioning
confidence: 78%
“…The typical crosssection of I/S fibers is shown in Figure 1. It was observed earlier [25] that a polymer ratio of 75/25, 25% being assigned to 'Sea' polymer or PE, had the best tear properties. In this study, nonwoven webs were produced with filaments that contain 75% of PA6 and 25% of PE, with different island counts.…”
Section: Fabric Formationmentioning
confidence: 89%
See 2 more Smart Citations
“…). Typical island counts are 1 (sheath core), 7, 12, 19, 37, 108, 216, and 360 . Hills Inc. (West Melbourne, FL) has reported fabrication of filaments containing up to 1200 islands, with the potential of achieving over 4000.…”
Section: Introductionmentioning
confidence: 99%